3 FIELD SQUADRON, SAEC (PART 1) - Van Zyl, A.E. (Scientia Militaria - South African Journal of Military Studies, 2012)
From Cape to Cullinan Although the Union Defence Act of 1912 had made provision for the establishment of engineering units as part of the Active Citizen Force of the Union Defence Forces (UDF). no steps had been taken initially to put this part of the Act into effect and the outbreak of war in August 1914 found the UDF without any engineers.